Alasan Peneliti Menggunakan Analisis Statistik Wilcoxon (Non Parametrik) - Zulkipli, Zulkipli; Zulfachmi, Zulfachmi; Rahmad, Abdul (Prosiding, 2024)
Research Models continue to develop or be modified by researchers. Over time, they also develop alternative models so that research can be carried out efficiently. Based on this problem, an initiation emerged to develop a simpler method, namely non-parametric statistics. There is one method that is quite often used by researchers, namely the Wilcoxon test. This study aims to explore the reasons researchers use the Wilcoxon Test (non-parametric). To provide a convincing picture of the research, a literature review was conducted by selecting articles from recently published peer-reviewed journals. Non-parametric statistics are statistical formulas that are used when the sample taken is likely to be relatively small. In addition, this method is also used to analyze data from test results, questionnaires, or other data collection instruments designed to ensure ideas and research results, regardless of whether the data is normal or not.